The Image of Felipe Pinglo Alva in the Historiography of Peruvian Musical Criollismo - Rojas Mesía, Omar Isaac (2018)
The “modern self” in Lima in the 1900s was a paradigm of a costal and criollo elite. It is in this context that Pinglo rises as an image of a composer easily identified with the popular, an image that was endorsed in 20th century historiographic accounts to the point of obfusicating not only other authors from this era, but also other facets of this musician that did not align with the Peruvianist pretensions of presenting Felipe Pinglo Alva as a savior of criolla music and the initial constructedness of the creation of this music. Nevertheless, a brief review of the corpus of works by this musician reveals that the number of social songs represents a minority of his creative work.